Women Empowerment Through ‘Aisyiyah’s Economic and Entrepreneurial Programs: Pemberdayaan Perempuan Melalui Program Ekonomi dan Kewirausahaan ‘Aisyiyah - Affandi, Akhmad; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Women’s empowerment through community-based organizations plays a vital role in strengthening the local economy and family welfare. Specific Background: The ‘Aisyiyah organization in Sidoarjo actively supports women’s micro, small, and medium enterprises (MSMEs) through training and cooperative initiatives. Knowledge Gap: Few studies discuss the operational strategies and socio-economic outcomes of ‘Aisyiyah’s empowerment programs. Aims: This study analyzes the role of the ‘Aisyiyah Community Organization in empowering women entrepreneurs to enhance MSME income in Sidoarjo Regency. Results: The study finds that women participating in ‘Aisyiyah’s programs experienced improved financial literacy, marketing capacity, and production efficiency, contributing to increased household income. Novelty: The integration of religious-based community movements with modern entrepreneurship development frameworks demonstrates a sustainable empowerment model. Implications: Strengthening digital marketing, cooperative networking, and financial management can enhance women’s economic resilience through ‘Aisyiyah’s initiatives. Highlights: ‘Aisyiyah promotes sustainable women entrepreneurship. Economic literacy increases household income levels. Community-based empowerment enhances business independence.